Omeprazole Inhibits Cell Proliferation and Induces G0/G1 Cell Cycle Arrest through Up-regulating miR-203a-3p Expression in Barrett’s Esophagus Cells - Hou, Yichao; Hu, Qiang; Huang, Jiao; Xiong, Hua (Frontiers in Pharmacology, 2018)
Existing data suggest that proton pump inhibitors (PPIs), particularly omeprazole, have significant antitumor action in monotherapy and or combination chemotherapy. Hedgehog (Hh) signaling pathway represents a leading candidate as a molecular mediator of Barrett’s esophagus (BE). Studies have indicated reduced miRNAs in BE progression, however, little is known about the latent anti-neoplasm effects of miRNAs in BE cells. Here, we investigated whether omeprazole could inhibit BE progression by regulating Hh pathway and explored the promising Hh-targeted miRNAs in BE cells. We conducted qRT-PCR and immunoblotting assay to evaluate the effects of omeprazole on the expression of Hh signaling components and miR-203a-3p in CP-A and CP-B cells. The promising target genes of miR-203a-3p were predicted by bioinformatics methods, and verified by luciferase assays and qRT-PCR. The effects of omeprazole on BE cell proliferation and cell cycle distribution were determined. The overexpression or silencing of miR-203a-3p was performed to test its anti-proliferative effects. Finally, rescue experiments that miR-203a-3p inhibitor alleviated the effects of omeprazole on decreasing the levels of Gli1 mRNA, protein and luciferase were performed. Mechanistic studies showed that omeprazole could inhibit the expression of Gli1 and the nuclear localization of Gli1. Moreover, we determined that omeprazole could selectively up-regulated the expression of miR-203a-3p, and Gli1 was a bona fide target of miR-203a-3p. MiR-203a-3p inhibitor alleviated the suppressing effects of omeprazole on Gli1 luciferase activity, mRNA and protein level. The functional assay suggested that omeprazole could dose-dependently inhibit BE cell growth and induce cell cycle arrest in G0/G1 phase. Additionally, overexpression and silencing of miR-203a-3p in BE cells disrupted cell cycle progress, resulting in suppressing and accelerating cell proliferation, respectively. Taken together, these data provide a novel mechanism of potentially antineoplastic effects for omeprazole through modulation of miR-203a-3p expression and thus suppressing Hh/Gli1 signaling in BE cells.